VALIDATION OF THE THEORETICAL-PRACTICAL CORRELATION BETWEEN SUTURE TECHNIQUES AND BIOCHEMICAL HEALING PARAMETERS: RESULTS OF A COURSE APPLIED TO MEDICAL STUDENTS - Bragança, Rian Rodrigues; Pedraça, Aline Dos Santos Atherly; Nascimento, Patrick Torres; dos Santos, João Vitor Silva; Reyes, Hermin Darío Ayala (Seven Editora, 2026)
The relationship between suturing techniques and biochemical parameters that affect the speed and quality of wound healing is a topic of great relevance to contemporary medical training. Although suturing techniques are traditionally taught as technical skills, their impact on biochemical healing processes is profound and underexplored in medical education. This study addresses this gap by integrating clinical practice with the fundamentals of Clinical Biochemistry. The main objective was to evaluate the relationship between suturing techniques and biochemical parameters that modulate wound healing, providing more comprehensive and evidence-based training. Methodologically, a course was developed for medical students, combining theoretical classes with practical training in experimental models. Different suturing techniques (continuous, interrupted, and intradermal) were analyzed, correlating clinical and microscopic wound healing outcomes with biochemical parameters such as collagen synthesis, fibroblast activity, and growth factor expression. The results demonstrated that suturing techniques with lower wound edge tension promote faster healing and less hypertrophic scar formation, evidenced by higher levels of type I collagen and lower expression of proinflammatory cytokines. It is concluded that integrating biochemical knowledge into the teaching of suturing techniques not only improves students' practical skills but also optimizes clinical outcomes, validating the effectiveness of the interdisciplinary teaching model.